Carbapenem and Colistin Resistance in Enterobacter: Determinants and Clones - Zong, Zhiyong; Feng, Yu; McNally, Alan (Trends in microbiology (Regular ed.), 2021)
Enterobacter is a globally important pathogen. Here we clarify its taxonomy and review recent developments in its resistance to carbapenem and colistin, illustrating that Enterobacter has a large arsenal of mechanisms to grow under antimicrobial pressure. Further studies are required to decipher colistin heteroresistance and understand why certain Enterobacter lineages have emerged clinically.